Dialectical relationship between law, constitutional law approach, and political economy in phenomenon of sharia economy driving MSMEs and halal industry: A literature review - Siti Hasanah; Firzhal Arzhi Jiwantara; Bayu Karunia Putra (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The development of Sharia economy in Indonesia has increasingly influenced the growth of micro, small, and medium enterprises (MSMEs) and the halal industry, particularly in Mataram City, West Nusa Tenggara. This phenomenon raises questions about the interplay between legal frameworks, constitutional law approaches, and political economy in shaping sustainable economic development. Methods: This study employs a qualitative literature review, analyzing scholarly articles, government reports, and policy documents related to Sharia economy, MSMEs, halal industry, and Indonesian constitutional and economic law. The aim is to understand how legal and political-economic perspectives interact in promoting economic initiatives rooted in Islamic principles. Findings: The analysis reveals that the integration of legal and constitutional approaches with political economy provides a comprehensive framework for understanding the growth of Sharia-based economic activities. In Mataram City, West Nusa Tenggara, MSMEs and halal industries thrive through supportive legal frameworks, government policies, and community-based initiatives that align with Islamic economic principles. This synergy demonstrates the dialectical relationship between law, politics, and economic practices in fostering inclusive and ethically grounded economic development. Conclusion: The study concludes that legal, constitutional, and political-economic integration is essential for promoting Sharia economy as a driver of MSMEs and halal industry, ensuring both compliance with Islamic principles and sustainable regional economic growth. Novelty/Originality of this article: This research offers a unique interdisciplinary perspective by combining constitutional law, political economy, and Sharia economic principles to reinterpret economic development in Mataram City, West Nusa Tenggara, highlighting the practical and theoretical implications of legally and ethically grounded economic policies.